Thermotolerant Capacity of Diverse Indonesian Lowland Holstein's Black and White Skin-Pigmentation Intensity - Prabowo, Sigid; Yani, Ahmad; Sumantri, Cece; Prihantoro, Iwan; Putra, Ahmad Romadhoni Surya; Achmad, Ferdian; Pramujo, Muhammad; Puspita, Poppy Satya; Güler, Serdar (Buletin Peternakan, 2025)
The lowland area of Indonesia has economic potential to develop as a major centre for dairy farming businesses. Still, there is a foremost matter: overheated irradiation immersed in damped air would increase the heat stress level. The present study was conducted to assess the heat stress tolerance level of lowland Indonesian Holstein cows, characterized by a dominant level of Black and White (B/W) pigmented skin coat. This study involved 34 heads of Holstein cows that were cared for in Eastern Jakarta. Breathing frequency (BF), rectum's warmth (RW), pulse rate (PL), white-skinned spot temperature (WSST), black-skinned spot temperature (BSST), average temperature rounded skin (ATRS), back region temperature (BRT), chest region temperature (CRT), upper-leg temperature (ULT), lower-leg temperature (LLT), skin's temperature (ST), body's temperature (BT), and heat tolerance coefficient (HTC) as variables were checked statistically with R 4.4.2 type software comprised correlation and independent t-test. Cows B/W classification performed with the imageJ 1.54g series program. Those analyses showed that most lowland Indonesian Holsteins were characterized by black-pigmented dominant cows (BDC). The pigmentation of both lateral sides of the body generated a significant correlation (p<0.05 and p<0.01) with several vital symptoms, including WSST, ATRS, ST, BT, and HTC, but only in the BDC Holstein class. The test of mean distinction between the two classes (BDC and WDC) produced statistically insignificant differences (p>0.05) in all measurable vital symptoms; all variables showed trends indicating that the BDC class had a greater response to heat stress. The BDC Holstein type selection base had high expectations of elevating the HTC score in Indonesian lowland cows, as the closing decision.